60 recipes for Apache CloudStack - Goasguen, Sebastien (O'Reilly, 2014)
This cookbook's handy how-to recipes help you quickly learn and install Apache CloudStack, along with several API clients, API wrappers, data architectures, and configuration management technologies that work as part of CloudStack's ecosystem.